Comparative In vitro Analysis of Push-Out Bond Strength of Different Root Canal Sealers to Root Dentin - Joyeta Ghosh; Bhagyesh J. Cheta; Yogesh V. Rathod; Richa Pathak; Shruti A. Nayak; K Vishnu Prasad (Journal of Pharmacy and Bioallied Sciences)
Aim: The study’s objective is to assess the bond strengths of four different endodontic sealers to root dentin using a push-out test technique. Material and Method: Sixty single-rooted teeth were selected and decoronated. Canal instrumentation was done using rotary files and divided into four groups (n = 15) based on the sealer used. Group 1: zinc oxide eugenol (ZOE)-based, Group 2: epoxy resin-based, Group 3: methacrylate-based, and Group 4: bioceramic. Following obturation with Gutta Percha, each tooth was prepared with root portions that were 2 mm thick at the apical and middle 1/3 so that universal testing equipment could measure the push-out bond strength. Tukey’s post hoc tests and one-way ANOVA were used to examine the data. Result: According to the results, group 4 had the strongest push-out relationship, followed by groups 3, 2, and 1, respectively. It can be concluded that the bioceramic sealers have superior bond strengths. Conclusion: Bioceramic sealers demonstrated the highest bond strengths to root dentin, outperforming methacrylate, epoxy resin, and zinc oxide eugenol sealers in the push-out test.